2017
DOI: 10.5539/jas.v9n7p80
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Screening of Leaves Compared to in situ and in vitro Calluses of Solanum aculeatissimum Jacq.

Abstract: Solanum aculeatissimum Jacq. is a shrub considered to have valuable medicinal potential in folk medicine in China and Nepal. The fruit extract is used for toothache, scabies, headache, dandruff and lice infestation. A limited number of reports address techniques of tissue culture for this plant. Therefore, the objective of the present study was to establish the species in vitro from seeds and subsequently to compare the production of primary and secondary metabolites in the plant's leaves in situ and in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The results of this study are in agreement with those found in leaves of Withania somnifera (L.) Dunal, where alkaloids and phenolic compounds have been identified (Munien et al, 2015). Higher production and accumulation of secondary metabolites have been observed in in vitro callus culture of Solanum aculeatissimum Jacq than in leaves cultured in vitro and in situ (Dantas et al, 2017). Research, Society and Development, v. 9, n. 8, e556985822, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.5822…”
Section: Histochemistrysupporting
confidence: 91%
“…The results of this study are in agreement with those found in leaves of Withania somnifera (L.) Dunal, where alkaloids and phenolic compounds have been identified (Munien et al, 2015). Higher production and accumulation of secondary metabolites have been observed in in vitro callus culture of Solanum aculeatissimum Jacq than in leaves cultured in vitro and in situ (Dantas et al, 2017). Research, Society and Development, v. 9, n. 8, e556985822, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.5822…”
Section: Histochemistrysupporting
confidence: 91%
“…Reports on the histochemical detection of different secondary metabolites carried out in plantlets grown in vitro are scarce [34,124,130]. Plants grown in vitro are continuously exposed to a defined microenvironment, providing nearly optimal conditions for plant proliferation, in contrast to marked variations of the growth conditions of field-grown plants.…”
Section: Secretion Of Secondary Metabolites In Vitromentioning
confidence: 99%